Creating social profiling to determine community needs and abilities in real work studies - Nasution, Mhd Sarif Muda; Kuswara, Lalu Indra Wadi; Dasrizal, Budiman (Universitas Ahmad Dahlan, 2024)
Real work study in general in carrying out empowerment in the community students bring their respective work programs that will be implemented in the community. most of the student work programs do not see the needs and abilities of the community. so that from the work programs made there is no concept of community sustainability. This research uses Qualitative Methods with Descriptive Analysis. This activity was carried out in RW 02 Ciputri Hamlet, Cisantana Village, Cigugur District, Kuningan Regency, West Java. Data obtained related to research through observation and interviews with community leaders and residents who are included in the scope of RW 02 Ciputri Hamlet. such as RT 01 to RT 06. Analysis of the effectiveness of making Social Profiling was carried out after the Real Work study was carried out for 40 days. The results of making Social Profiling can be summarized for each RT according to the needs and abilities of its citizens. From the application of Social Profiling can provide the accuracy of the Real Work study work program through data obtained from the aspirations of residents. so that through the work program can be sustainable as an effort in social development